A role for synaptonemal complex in meiotic mismatch repair. Issue 2 (15th December 2021) - Voelkel-Meiman, Karen; Oke, Ashwini; Feil, Arden; Shames, Alexander; Fung, Jennifer; MacQueen, Amy J
Abstract: A large subset of meiotic recombination intermediates form within the physical context of synaptonemal complex (SC), but the functional relationship between SC structure and homologous recombination remains obscure. Our prior analysis of strains deficient for SC central element proteins demonstrated that tripartite SC is dispensable for interhomolog recombination in Saccharomyces cerevisiae. Here, we report that while dispensable for recombination per se, SC proteins promote efficient mismatch repair at interhomolog recombination sites. Failure to repair mismatches within heteroduplex-containing meiotic recombination intermediates leads to genotypically sectored colonies (postmeiotic segregation events). We discovered increased postmeiotic segregation at THR1 in cells lacking Ecm11 or Gmc2, or in the SC-deficient but recombination-proficient zip1[Δ21-163] mutant. High-throughput sequencing of octad meiotic products furthermore revealed a genome-wide increase in recombination events with unrepaired mismatches in ecm11 mutants relative to wildtype. Meiotic cells missing Ecm11 display longer gene conversion tracts, but tract length alone does not account for the higher frequency of unrepaired mismatches. Interestingly, the per-nucleotide mismatch frequency is elevated in ecm11 when analyzing all gene conversion tracts, but is similar between wildtype and ecm11 if considering only those events with unrepaired mismatches. Thus, in both wildtype and ecm11 strains a subset of recombination events is susceptible to a similar degree of inefficient mismatch repair, but in ecm11 mutants a larger fraction of events fall into this inefficient repair category. Finally, we observe elevated postmeiotic segregation at THR1 in mutants with a dual deficiency in MutSγ crossover recombination and SC assembly, but not in the mlh3 mutant, which lacks MutSγ crossovers but has abundant SC. We propose that SC structure promotes efficient mismatch repair of joint molecule recombination intermediates, and that absence of SC is the molecular basis for elevated postmeiotic segregation in both MutSγ crossover-proficient ( ecm11, gmc2 ) and MutSγ crossover-deficient ( msh4, zip3 ) strains.